2022
DOI: 10.3390/ijms23105626
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Dysfunction Induced by Extracellular Neutrophil Traps Plays Important Role in the Occurrence and Treatment of Extracellular Neutrophil Traps-Related Disease

Abstract: Many articles have demonstrated that extracellular neutrophil traps (NETs) are often described as part of the antibacterial function. However, since the components of NETs are non-specific, excessive NETs usually cause inflammation and tissue damage. Endothelial dysfunction (ED) caused by NETs is the major focus of tissue damage, which is highly related to many inflammatory diseases. Therefore, this review summarizes the latest advances in the primary and secondary mechanisms between NETs and ED regarding infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 192 publications
(229 reference statements)
1
7
0
1
Order By: Relevance
“…It has been shown that NETs, apart from their beneficial role in clearing the invading microorganism, are implicated in the pathogenesis of many diseases in which endothelial dysfunction is present, such as sepsis and cardiovascular diseases. Therefore, there has been a growing interest in studying the role of NETs in endothelial dysfunction in sepsis ( 119 ). In vitro studies suggest that NETs can promote endothelial dysfunction, as indicated by increased endothelial expression of ICAM-1, VCAM-1, E-selectin, TF, and vWF ( 60 , 62 , 109 , 120 123 ).…”
Section: Neutrophils In Immunothrombosismentioning
confidence: 99%
“…It has been shown that NETs, apart from their beneficial role in clearing the invading microorganism, are implicated in the pathogenesis of many diseases in which endothelial dysfunction is present, such as sepsis and cardiovascular diseases. Therefore, there has been a growing interest in studying the role of NETs in endothelial dysfunction in sepsis ( 119 ). In vitro studies suggest that NETs can promote endothelial dysfunction, as indicated by increased endothelial expression of ICAM-1, VCAM-1, E-selectin, TF, and vWF ( 60 , 62 , 109 , 120 123 ).…”
Section: Neutrophils In Immunothrombosismentioning
confidence: 99%
“…myeloperoxidase-ANCA2 in most patients with MPA are positive which can be mainly evoked by the ANCA-mediated over-activation of neutrophils and release of inflammatory cytokines, reactive oxygen species and plasmin. [4] The excessive activation of neutrophils by ANCA could result in the formation of Neutrophil extracellular traps, which are involved not only in ANCA-mediated vascular injury but also in the production of ANCA itself. [5] The third mechanism refers to the anti-diuretic hormone theory proposed by Largeau et al, namely the overproduction of what is known as arginine vasopressin in humans.…”
Section: Discussionmentioning
confidence: 99%
“…These mechanisms result in collagen production and vascular injury. 43,44 Compelling evidence highlights the central role of T-cell activation, contributing to vascular alterations through the release of proinflammatory cytokines and organ damage. 36 Specifically, proinflammatory T cells, including CD4 + Th1 and Th17 cells, CD8 + T cells, and γδ-T cells have been documented in resistance vessels of patients with hypertension.…”
Section: Immune-mediated Responsesmentioning
confidence: 99%